An Example for All the Land : Emancipation and the Struggle over Equality in Washington, D.C. - Masur, Kate (Book collections on Project MUSE., 2010)
Masur offers the first major study of Washington during Reconstruction in over fifty years. Masur's panoramic account considers grassroots struggles, city politics, Congress, and the presidency, revealing the District of Columbia as a unique battleground in the American struggle over equality.